Anterior and posterior corneal elevation after orthokeratology and standard and customized LASIK surgery - Queirós, A. (2011)
Purpose: To quantify the changes in the elevation topography of the front and back corneal surfaces after three different refractive treatments for correcting myopia with standard and custom laser in situ keratomileusis (LASIK) and orthokeratology using corneal refractive therapy.Methods: We evaluated 20 eyes undergoing orthokeratology for correction of myopia spherical equivalent (mean +/- SD=-3.41 +/- 0.76 D), 18 eyes undergoing custom LASIK surgery (mean +/- SD=-4.14 +/- 0.89 D), and 23 eyes undergoing standard LASIK (mean +/- SD=23.61 +/- 0.67 D). The values of front and back corneal surfaces were derived by using Pentacam (Oculus, Inc. GmbH, Wetzlar, Germany) before and at least 3 months after each treatment, in the center of the cornea and 4 points to each side of the horizontal meridian at intervals of 1 mm.Results: Corneal elevation data before treatment were not statistically different between patients in either group (P>0.070, for back and front elevation). After treatment, both surgical procedures significantly increased the positive value of the front elevation beyond an area of 6 mm. The opposite trend was found within the central 5 mm of the cornea, presenting a statistically significant decrease in elevation (P<0.001). In the case of orthokeratology, the elevation experienced a minor but a statistically significant reduction in the central region (P<0.001). On the back surface, the elevation did not undergo statistically significant alterations in any of the procedures and none of the items discussed (P>0.285).Conclusions: Differences in front corneal elevation changes between LASIK and orthokeratology reveal a much different mechanism for producing corneal power subtraction. The back corneal surface does not suffer significant changes after surgical and nonsurgical treatments for the correction of myopia.